Congenital syphilis in 2 children in a Bolivian prison - L. Gétaz; K.M. Posfay-Barbe; N. Cossio; M. Villarroel-Torrico (Sociedad Española de Sanidad Penitenciaria, 2017)
Abstract In 2013 a cross-sectional study was carried out that revealed 28 cases of active syphilis amongst female inmates in a prison of Cochabamba, Bolivia. A search was conducted for congenital syphilis amongst the children that lived with the infected mothers. It is important to note the prevention of perinatal transmission of syphilis by systematic screening of pregnant women and appropriate treatment given by trained professionals within the prison environment, which represents a key population for controlling this disease, which is responsible for causing severe complications.